2003
DOI: 10.1210/en.2002-220984
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Novel Human Guanine Nucleotide Exchange Factor Src Homology 3 Domain-Containing Guanine Nucleotide Exchange Factor (SGEF) and of C-Terminal SGEF, an N-Terminally Truncated Form of SGEF, the Expression of Which Is Regulated by Androgen in Prostate Cancer Cells

Abstract: In searching for androgen-responsive genes in human prostate cancer cells, we have isolated two cDNAs that encode alternate forms of a novel Src homology 3 domain-containing guanine nucleotide exchange factor (SGEF). The SGEF mRNA is widely expressed in human tissues, and the predicted 871-amino acid SGEF protein contains Dbl homology and pleckstrin homology domains as well as an N-terminal proline-rich domain, a C-terminal Src homology 3 domain, and two nuclear localization signals. The second cDNA encodes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…64,65) Moreover, a novel putative human Rho GEF designated Src homology 3 (SH3) domain-containing guanine nucleotide exchange factor (SGEF) provides a direct link for cross-talk between the androgen receptor and Rho GTPase signaling pathways in prostate cancer cells. 66) In consequence, the down-regulated ARHGEF16 gene by kojic acid may suppress or deactivate the tumor progression of A375 melanoma cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…64,65) Moreover, a novel putative human Rho GEF designated Src homology 3 (SH3) domain-containing guanine nucleotide exchange factor (SGEF) provides a direct link for cross-talk between the androgen receptor and Rho GTPase signaling pathways in prostate cancer cells. 66) In consequence, the down-regulated ARHGEF16 gene by kojic acid may suppress or deactivate the tumor progression of A375 melanoma cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, both Trio and Kalirin are implicated as a catalyst for RhoG activation during neurite outgrowth (Blangy et al, 2000;May et al, 2002). SGEF mRNA was detected in brain extracts (Qi et al, 2003), providing the possibility that a similar function(s) exists for SGEF. At the same time, the expression of SGEF in hematopoietic cell lines is noteworthy when considering that RhoG regulates gene transcription in B and T cells and homozygous disruption of the RhoG gene in mice results in elevated levels of immunoglobulins in serum and a mild increase in lymphocyte response to antigen (Vigorito et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…SGEF (SH3-containing Guanine Nucleotide Exchange Factor) was initially found in a screen for androgen-responsive genes in human prostate (Qi et al, 2003). Two alternatively transcribed forms of SGEF gene were isolated, one which encodes the full-length molecule of 871 amino acids and the other an androgen-inducible splice-variant of 139 amino acids that contains only a small segment of the pleckstrin homology (PH) domain and the entire carboxyl Src homology 3 (SH3) domain.…”
Section: Introductionmentioning
confidence: 99%
“…Next, they investigated how SopB activates RhoG and discovered that SGEF (SH3-containing guanine nucleotide exchange factor) was recruited to ruffles in a SopB-dependent manner and that it was required for SopB-dependent RhoG activation. SGEF is a recently identified RhoG exchange factor that stimulates macropinocytosis (8,42). They also demonstrated that, while not involved in invasion, SopB activation of Cdc42 modulates nuclear responses to serovar Typhimurium infection.…”
Section: Hijacking Of Host Cell Signalingmentioning
confidence: 98%